Kontribusi Modal Sendiri Terhadap Rentabilitas Pada PT. Kimia Farma, Tbk. Di Bursa Efek Indonesia - Dini Arifian; Euis Ajizah; Siti Nina Herlina (E-Journal Studia Manajemen, 2012)
Equity earnings are often also referred to as Return On Equity (ROE), which is the ability of a company with its own capital to work on it to make a profit. Profit calculated to calculate the profitability of equity is the net profit after tax. While the capital are taken into account only their own capital contained in the company. So the profitability of own capital is the ratio between the amount of income available for owners of their own capital on the one hand by the amount of own capital on the other hand, are discussed in this study own capital generally rise and fall of their own capital in PT. Kimia Farma Tbk. Occurs because the rise and fall of profits or proceeds from the sale of the products sold in the market by PT. Kimia Farma Tbk, an increase in equity where the increase in equity where In 2007 the increase in equity of 0.16% compared to 2006 amounting to 0,00% since the early years of observation, in 2008 a decline of 0.08% of equity capital , In 2009 a decline of 0.02% of its own capital, in 2010 there was an increase of 0.31% of equity capital, In 2011 a decline of 0.20% of equity capital.